2018
DOI: 10.3390/f9070384
|View full text |Cite
|
Sign up to set email alerts
|

Investment Uncertainty Analysis in Eucalyptus Bole Biomass Production in Brazil

Abstract: Forestry investment projects for the biomass production of the eucalyptus bole can be characterized by uncertain environments, which result in economic risk to the forest producer, however that can be measured by applying probabilistic techniques. This was our motivation and justification for analyzing the economic-financial viability of different silvicultural practices for eucalyptus bole biomass production under conditions of uncertainties, running Monte Carlo method for risk management. The experiment was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…argue that extending the harvest age has a lower opportunity cost in low-productivity environments, and therefore the cost of conserving the stand as well as the amount of carbon stored are lower, discouraging landowners to enter the voluntary carbon market when faced with a xed payment for forest carbon.For landowners who have mature forests and seek a contract paying for marginal carbon sequestration over the next few years, only those who established eucalyptus will be able to bene t and, again, those who cultivate PIRA will not bene t if there are no government incentives.When analysing stochastic valuation, the decision to opt for carbon payment is more sensitive to the price of carbon captured, roundwood and the discount rate. Similar results were found by Fischer et al(2017),Simões et al (2018) andMei and Clutter (2022) in investigations analogous to ours using Monte Carlo simulation. Similar to them, it was found that the optimum rotation age does not deviate much from that de ned by the Faustmann model when roundwood prices are above the price of the hypothetical carbon contracts.In conclusion, considering that planted forests are a nature-based solution to contain the climate change we are experiencing, additional forest carbon from eucalyptus-planted forests becomes an effective option if we extend their harvest age.…”
supporting
confidence: 93%
“…argue that extending the harvest age has a lower opportunity cost in low-productivity environments, and therefore the cost of conserving the stand as well as the amount of carbon stored are lower, discouraging landowners to enter the voluntary carbon market when faced with a xed payment for forest carbon.For landowners who have mature forests and seek a contract paying for marginal carbon sequestration over the next few years, only those who established eucalyptus will be able to bene t and, again, those who cultivate PIRA will not bene t if there are no government incentives.When analysing stochastic valuation, the decision to opt for carbon payment is more sensitive to the price of carbon captured, roundwood and the discount rate. Similar results were found by Fischer et al(2017),Simões et al (2018) andMei and Clutter (2022) in investigations analogous to ours using Monte Carlo simulation. Similar to them, it was found that the optimum rotation age does not deviate much from that de ned by the Faustmann model when roundwood prices are above the price of the hypothetical carbon contracts.In conclusion, considering that planted forests are a nature-based solution to contain the climate change we are experiencing, additional forest carbon from eucalyptus-planted forests becomes an effective option if we extend their harvest age.…”
supporting
confidence: 93%
“…As advised by O' Hagan et al (2006), Leal et al (2007), Briggs et al (2012), and Simões et al (2018), based on the opinion of forestry experts, a volatility of 30.0% and a drift of 10.0%, both related to the behavior of the price of T. ciliata wood, were assumed. Consequently, the Monte Carlo method simulation was performed with 100,000 iterations, with the use of the @Risk Copyright © 2020 software (Palisade Corporation, 2021).…”
Section: Volatility Of the Investment Project In Planted Forests With...mentioning
confidence: 99%
“…Eucalyptus is included in the woody biomass SCM category and is considered one of the most commercial woody crops cultivated for bioenergy production. In [43], the economic viability of various operational practices regarding whole eucalyptus tree trunk production was analyzed under varying production and economical parameters. To analyze risk management a Monte Carlo analysis was run.…”
Section: Strategic Planningmentioning
confidence: 99%